2007
DOI: 10.1016/j.hrthm.2007.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Transmural and endocardial Purkinje activation in pigs before local myocardial activation after defibrillation shocks

Abstract: Background-Earliest recorded post-shock myocardial activations in pigs originate in the subepicardium of the apex and lateral free wall of the left ventricle (LV) 30−90 ms after the shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…This different distribution of earliest postshock activation in the two species draws our attention to the Purkinje fibers involved in the creation and propagation of earliest activation, because in the pig the Purkinje fibers extend from the endocardium almost to the epicardium, while in dogs the Purkinje fibers are limited to the subendocardium. Dosdall et al [28] demonstrated that the Purkinje system is active during the early postshock activation cycles following DFT level shocks with the same shock electrode configuration as ours. Therefore, the endocardial basket in the LV is capable of detecting the earliest activation pattern after the defibrillation shock in the canine model.…”
Section: Alteration Of Apd and Qt Interval By Pinacidilsupporting
confidence: 61%
“…This different distribution of earliest postshock activation in the two species draws our attention to the Purkinje fibers involved in the creation and propagation of earliest activation, because in the pig the Purkinje fibers extend from the endocardium almost to the epicardium, while in dogs the Purkinje fibers are limited to the subendocardium. Dosdall et al [28] demonstrated that the Purkinje system is active during the early postshock activation cycles following DFT level shocks with the same shock electrode configuration as ours. Therefore, the endocardial basket in the LV is capable of detecting the earliest activation pattern after the defibrillation shock in the canine model.…”
Section: Alteration Of Apd and Qt Interval By Pinacidilsupporting
confidence: 61%
“…Furthermore, patterns of postshock propagation on the epicardium of the rabbit model match well these determined experimentally, 15 with no evidence of micro-VE contribution. Finally, the ventricular model did not include Purkinje network; depolarization-induced automaticity from Purkinje fibers could be a different mechanism for PA origin 29 in addition to those presented here. …”
Section: Study Limitationsmentioning
confidence: 89%
“…In fact, here we observed in the simulations that postshock propagation within the LV midmyocardium was strongly dependent on preshock state. However, the concepts proposed here do not limit the origin of the initiating PAs; these might have alternative origins, such as Purkinje fibers (Dosdall et al, 2007). The tunnel hypothesis is independent of the origin of wavefronts that propagate through it.…”
Section: Implications Of the Tunnel Propagation Hypothesismentioning
confidence: 92%
“…Understanding the origins of the isoelectric window is thus of great importance for uncovering the mechanisms of defibrillation failure. Various hypothesis have been proposed for the existence of the isoelectric window, including virtual electrodeinduced propagated graded response (Trayanova et al, 2003), calcium sinkholes (Hwang et al, 2006), and activations emanating from Purkinje fibers (Dosdall et al, 2007); however, the mechanisms responsible for it remain inconclusive. In this context, we hypothesized that submerged "tunnel propagation" of postshock activation (PA) through shock-induced intramural excitable areas underlies both fibrillation induction and failed defibrillation by shocks as well as the existence of an isoelectric window.…”
Section: Introductionmentioning
confidence: 99%